The Role of the Defense Industry in Supporting Economic Growth: A Comparison Between Global Trends and Indonesia’s Challenges - Agus Sutisna; Hendra Wulan; Guntur Eko Saputro (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2025)
Purpose: This study aims to analyze and compare the role of the defense industry in supporting economic growth, focusing on the gap between global trends and the realities faced in Indonesia.Method: A systematic literature review (SLR) following the PRISMA protocol was employed for this research. It analyzes 48 articles from 2014 to 2024 using both descriptive and bibliometric methods to synthesize the findings.Results: A significant gap between global trends and Indonesia's reality is evident. While the defense industry globally has consistently been a key economic driver through increased exports, investment, and innovation, in Indonesia, its role remains largely untapped. The industry is hindered by various challenges, such as a high dependence on imported weapons and components, which limits export capabilities, suboptimal human resources, inconsistent domestic orders, and a minimal R&D budget that drains resources without fostering competitive innovation.Practical Implications for Economic Growth and Development: This study offers an evidence-based diagnosis of the main challenges the Indonesian government must address. The findings can inform the development of more effective policies to promote the defense industry’s independence, enabling its transition from a potential contributor to a real driver of economic growth and development.Originality/Value: This study is novel in two ways: first, it is the first SLR comparing the global and Indonesian contexts, and second, it uniquely applies the